Workshop Urgensi Pemanfaatan Media Pembelajaran Inovatif dalam Bimbingan dan Konseling Di SD - A. Hari Witono; Mansur Hakim; I Ketut Widiade; Heri Hadi Saputra; Tamy Amalia Wijaya; Heri Setiawan (Educational Consultant & Counseling Career (EC3) Mataram, 2024)
The implementation of guidance and counseling in elementary schools is the task of the class teacher. This is related to the rare availability of BK teachers or special counselors on duty in elementary schools. In fact, based on the results of observations during the implementation of the research in June-July 2022 at SD Negeri 1 Kekeri, teachers have not implemented BK services optimally. Therefore, the PGSD FKIP Universitas Mataram service team carried out community service with the title